Textuality, culture and scripture : a study in interrelations - Kort, Wesley A. (Anthem Press, an imprint of Wimbledon Publishing Company, 2020)
(3z (BTextuality, Culture and Scripture, (3y (Ba study of the necessary and close relations between the three concepts, describes the prominent role of texts and textuality in Western modernity and the exchange of textual for material understandings of culture that becomes apparent in the middle of the twentieth century. Taking its starting point in the turn or return in cultural studies to textuality, the argument addresses the necessary role of texts and textuality in cultural, group and personal identities. Central to the argument is the thesis that (3z (Bscripture, (3y (Brather than an occasional or optional textual category, should be seen as playing a necessary role in an adequate textual theory.